THE STRUCTURE AND PROCESS OF SERA INSTITUTION IN CONFLICT RESOLUTION IN SILTIE SOCIETY - Ezedin Fedlu Nuri (International Journal of Innovations in Engineering Research and Technology, 2023)
The structure and process of sera institution in conflict resolution in the Siltie society has rarely been treated in previous literatures. Thus, this study mainly aimed to fill this gap by examining the structure, process and major rituals of sera institution in resolving conflicts in Siltie Society. The study employed a descriptive qualitative research design. The researcher has collected data from primary and secondary sources. The data collected were organized thematically and analyzed qualitatively. The findings revealed that Sera institution in Siltie society has its unique structures and process for conflict resolution such as steps of hearing, examination of parties, judgments process, appeals, methods of decision enforcement and rituals. Finally based on the findings of the research, the researcher has recommended some key points such as high promotion, research, artistic activities such documentaries have to be done on Sera for the case of Siltie society to promote and best benefit it.